2021
DOI: 10.3389/fimmu.2021.636108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tenascin-C on Radiotherapy in a Novel Syngeneic Oral Squamous Cell Carcinoma Model With Spontaneous Dissemination to the Lymph Nodes

Abstract: Radiotherapy, the most frequent treatment of oral squamous cell carcinomas (OSCC) besides surgery is employed to kill tumor cells but, radiotherapy may also promote tumor relapse where the immune-suppressive tumor microenvironment (TME) could be instrumental. We established a novel syngeneic grafting model from a carcinogen-induced tongue tumor, OSCC13, to address the impact of radiotherapy on OSCC. This model revealed similarities with human OSCC, recapitulating carcinogen-induced mutations found in smoking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The tumor immune microenvironment has been highly researched(26). Lots of evidences showed OSCC is an immune-suppressive disease (27). Immunotherapy is a novel approach for restoring anti-tumor immune responses and overcoming tumor cell immune escape mechanisms(28).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor immune microenvironment has been highly researched(26). Lots of evidences showed OSCC is an immune-suppressive disease (27). Immunotherapy is a novel approach for restoring anti-tumor immune responses and overcoming tumor cell immune escape mechanisms(28).…”
Section: Discussionmentioning
confidence: 99%
“…PDGFRA (platelet derived growth factor receptor alpha) mutations cause a variety of heterogeneous gastrointestinal mesenchymal tumors (Ricci et al, 2015), and TKIs inhibiting the most common driving mutations in KIT or PDGFRA might have brought about radical changes in treating gastrointestinal stromal tumors in the past 20 years (Zalcberg, 2021). TNC (enascin-C) is a large extracellular matrix glycoprotein that promotes cell adhesion and tissue remodeling, and is involved in the transduction of cellular signaling pathways (Spenlé et al, 2021). These findings encourage us to explore the molecular mechanisms of these genes in BLCA in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In gliomas, KO of CD47 induced TNC, which promoted phagocytosis and revealed a poorly understood immune crosstalk that is affected by TNC ( Ma et al, 2019 ). Investigating gene expression patterns revealed that tumors with host-derived TNC upregulated several genes associated with antigen processing and presentation, shedding light on a potential, but as yet poorly understood, DAMP function of TNC in cancer ( Deligne et al, 2020 ; Spenlé et al, 2021 ; Murdamoothoo et al, 2021 ). The balance between pro- and anti-tumorigenic effects of TNC on immune surveillance might regulate whether a tumor thrives or regresses ( Fig.…”
Section: Tenascin-c Promotes Plasticity Invasion and Metastasismentioning
confidence: 99%